ANALISIS SIMPANG EMPAT BERSINYAL LABUAH BASILANG KOTA PAYAKUMBUH - Eka Fitra Novirman; Helga Yermadona; Yorizal Putra (Ensiklopedia Research and Community Service Review, 2022)
Payakumbuh is one of the cities in Indonesia which is located precisely in the province of West Sumatra. The rapid growth of cities such as Payakumbuh has an impact on the development of various systems. The increase in population density greatly affects the level of traffic congestion in Payakumbuh City. Transportation is an aspect of life that has a very important role in supporting activities that meet human needs. The rapid population growth in Payakumbuh City will result in an increase in demand for transportation services and an increase in the number of private vehicles. This will have an impact on traffic problems, namely congestion, delays and queues on roads in the city of Payakumbuh. Efforts to overcome these problems can be done by regulating traffic and improving the presentation of roads so that they can meet the needs of pedestrians as much as possible Keywords: Capacity, Delay at Labuah Basilang Intersection